PENGEMBANGAN PROGRAM KEWIRAUSAHAAN DI PERGURUAN TINGGI - Elizar Elizar (Edukasi Lingua Sastra, 2018)
Entrepreneurship Education in college is important for all profession. Entrepreneurship education has been developed in almost all universities in Indonesia. College as one of the means and facitating role in shaping the young generation has an obligation to train and motivate the studens to give to become savvy genaration, independent, creative, innovative and able to create business oportunities. Thus, every college immediately toward sole discreation to balance between higher education reasearch institusion with entrepneurs forming institutions. Alumni are required to be innovative and creative in terms of their personal development through the creation of level playing field, so that future expected withextensive job creation, economic growth in the region will increase. An entrepreneur is students who exploits his/her creativity to create something valuable either in the form of tangible or intangible.